Motivational techniques to develop and strengthen the inter-learning of the English language in the students of the 9th year of basic education of the Machala house school and Juan Henriquez Coello high schools in the city of Machala during the academic period of 2010 - 2011. - Martínez Peña, Bairon Alexander; Yunga Rodríguez, Caty Fabiola (Machala : Universidad Técnica de Machala, 2011)
El objetivo de esta tesis es determinar como la motivación influye en los estudiantes cuando ellos aprenden el idioma inglés, la motivación es un aspecto relevante dentro del campo educativo puesto que permite que los alumnos se encuentren activos durante el proceso de inter-aprendizaje. El trabajo investigativo nos ha permitido establecer la manera en que los alumnos deben ser motivados durante las clases de inglés. Para esto hemos desarrollado divertidas actividades con el fin de ayudar a los estudiantes a participar de forma dinámica y activa así como, estas actividades les permiten mejorar y desarrollar las cuatros habilidades del idioma inglés de esta manera forma ellos aprenden en un ambiente relajado y confortable.
The objective of this thesis is to determine how motivation influences students when they learn the English language , motivation is an important factor in the education field because it allows students to assets are in the process of mutual learning . The research work has enabled us to establish how students should be motivated for English classes . For this we have developed fun activities in order to help students to participate actively and dynamically and these activities allow them to improve and develop the four skills of English so how they learn in a relaxed and comfortable atmosphere.
Keywords: MOTIVATIONAL; DEVELOP; STRENGTHEN; LANGUAGE